Reliability and validity of the Shona version of the Exercise Benefits and Barriers Scale in Zimbabwean adult people living with HIV/AIDS - Dambi, Jermaine M.; Domingue, Ben; Abas, Melanie; Chibanda, Dixon; Esterhuizen, Tonya M. (Frontiers in Psychiatry, 2023)
Introduction: Despite the widely known benefits of physical activity (PA), only 25% of people living with HIV (PLHIV) meet the WHO-recommended minimum PA levels. Consequently, it is essential to understand PA barriers and facilitators using objective measures. Although the Exercise Benefits and Barriers Scale (EBBS) is extensively used, its psychometric evidence is fragmented and has not been previously validated in PLHIV. This study aimed to translate and validate the EBBS Shona version in Zimbabwean PLHIV. Methods: A cross-sectional study was used to recruit 567 PLHIV from four (4/9) randomly selected polyclinics (primary healthcare facilities) in urban Harare, Zimbabwe. We recruited adult patients (aged ≥ 18 years) with a confirmed diagnosis of HIV. Participants had to be willing to provide informed consent, not acutely unwell, and proficient in the Shona language. We used a forward-backwards translation method to translate the EBBS from English to Shona, a native Zimbabwean language. After crosscultural adaptation, we pretested the draft version in 10 PLHIV to assess the face validity, understandability and cultural appropriateness using semi-structured interviews. Thereafter, the EBBS was administered to 567 consecutively-selected PLHIV. Factor analyses were performed for construct validity evaluation.Results: Most participants were female (72.5%) and reached secondary/high school (78.8%), with a mean age of 39.9 (SD 12.1) years. The EBBS-Shona version yielded a four-factor solution consisting of three benefits factors and one barrier factor against the originally postulated six-factor structure. The EBBS-Shona yielded α=0.85 and intraclass correlation coefficient= 0.86, demonstrating excellent reliability. Increased perception of exercise benefits was positively correlated with increased reports of physical activity, higher health-related quality of life and lower psychiatric morbidity; evidence for construct validity. Discussion: This study demonstrates the validity and reliability of the EBBS-Shona version in Zimbabwean PLHIV. The EBBS-Shona version can be used for research and clinical purposes to glean data to inform the development, implementation, and evaluation of bespoke PA interventions for PLHIV.